2018
DOI: 10.1590/1983-21252018v31n404rc
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhization Stimulant in Soybean Associated With Phosphate Fertilization in Oxisols

Abstract: The use of stimulants in the establishment of arbuscular mycorrhizal fungi has great potential in contributing to P uptake by plants. This study aimed to evaluate the effect of isoflavonoid formononetin as mycorrhization stimulant on soybean associated with phosphate fertilizer in Oxisols with intermediate (OPi) and low (OPl) phosphorus availability, in the Cerrado region of Piauí. The experiment in each soil consisted of randomized blocks design in a 4×4 factorial scheme, with four replications. The treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
1
1
0
2
Order By: Relevance
“…On all media compositions, mycorrhizal inoculation treatments of I1, I2, and I3 resulted in higher chlorophyll content and P concentration in shoot tissues compared with the treatments without mycorrhizal inoculation (I0). This result is consistent with the report of Andrade et al (2018) that the mycorrhizal inoculation increased P concentration and P uptake of soybean on Oxisols. Gheisari Zardak et al (2017) found that the application of AM increased the accumulation of P in plant tissues and simultaneously stimulated plant growth.…”
Section: Discussionsupporting
confidence: 93%
“…On all media compositions, mycorrhizal inoculation treatments of I1, I2, and I3 resulted in higher chlorophyll content and P concentration in shoot tissues compared with the treatments without mycorrhizal inoculation (I0). This result is consistent with the report of Andrade et al (2018) that the mycorrhizal inoculation increased P concentration and P uptake of soybean on Oxisols. Gheisari Zardak et al (2017) found that the application of AM increased the accumulation of P in plant tissues and simultaneously stimulated plant growth.…”
Section: Discussionsupporting
confidence: 93%
“…In the seedling phase this can be of key importance in decreasing the time spent developing the nursery. Consequently, the use of stimulants to establish the of mycorrhizal fungi colonization of root systems has great potential in agriculture (ANDRADE et al, 2018). The use of formononetine, has been shown to stimulate mycorrhization of native species roots, facilitating colonization by mycorrhizal fungi.…”
Section: Methodsmentioning
confidence: 99%
“…Além da adequada composição do substrato para a produção de mudas de qualidade, as plantas que se beneficiam da simbiose com fungos micorrízicos podem, também, apresentar maiores incrementos na massa seca de raízes e parte aérea (SILVA et al, 2017), o que pode ser fundamental em fase de muda para diminuir o tempo de permanência no viveiro. O uso de estimulantes para estabelecer a colonização de fungos micorrízicos em raízes tem grande potencial na agricultura (ANDRADE et al, 2018). O uso da formononetina, como estimulante de micorrização nas culturas, tem demonstrado capacidade de estimular a colonização com espécies nativas de fungos micorrízicos.…”
Section: Introducãounclassified
“…Muitas micorrizas são estimuladas pela presença de compostos isoflavonóides formonetina, potencializando a fixação de fósforo para as plantas de soja, sendo reconhecido acréscimos de produtividade e eficiência agronômica de 15 kg ha -1 de grãos para cada kg há de fósforo aplicado no solo (ANDRADE et al, 2018).…”
Section: Introductionunclassified